Values oriented leadership: Conceptualization and preliminary results in Slovakia - Anna Lašáková; Ľubica Bajzíková; Ivana Blahunková (Verslas: Teorija ir praktika / Business: Theory and Practice, 2019)
The paper builds on the current trend in scholarly literature that reflects leadership from an ethical perspective. It introduces a new conceptualization of the values oriented leadership (VOL) and based on results of a pilot study, it informs on the level of VOL in the Slovak business environment and on systematic differences in VOL related to multiple individual and organizational factors. Contrary to the literature, results show that the VOL does not differ substantially between female and male leaders. Furthermore, this study adds to the current leadership ethics research also in that it includes two rarely investigated factors - the "length of leader-follower cooperation" and the "frequency of leader-follower interaction". Both show an effect on the perceived VOL level; the theorized positive correlation with the frequency of leader-follower interaction is confirmed, nevertheless, somewhat surprisingly, results imply that the length of leader-follower cooperation affects negatively leader's perceived ethicality at work. This study proves also differences in VOL based on regional company location and company size, with leaders in small companies rated significantly lower in VOL than leaders in large companies. The difference in VOL between leaders in Slovak-owned and foreign-owned companies is not established. Yet, compared to the private sector, this study confirms significantly lower VOL in the state-owned companies.
Keywords: M12; M14; 650; ethics; leadership; ethical leadership; values; values oriented leadership; Slovakia; CEE